Strategi Pemasaran Pada UMKM Ikhtiar dengan Analisis SWOT dan Weighted Aggregated Sum Product Assesment (WASPAS) - Jufriyanto, Moh. (JISI: Jurnal Integrasi Sistem Industri, 2023)
Marketing strategy is a way to achieve the goals of business planning. A good marketing strategy will have a great influence on the marketing process of its products. Ikhtiar MSMEs is one of the MSMEs engaged in the production of chips. One of the productions is taro chips. The problems that occur in Ikhtiar MSMEs are the sales of taro chips that have fluctuated, the emergence of competitors who sell chip products, and the process of improving marketing after the Covid-19 outbreak. Therefore, the study aims to formulate and determine the right marketing strategy for Ikhtiar MSMEs. The study used the SWOT analysis method and weighted aggregated sum product assessment (WASPAS). From the results of the study obtained three alternative marketing strategies that are recommended and can be considered. These strategies include the A3 strategy (Utilizing and increasing promotion through existing online media), the A1 strategy (Improving services to consumers), and the A2 strategy (Following training on marketing activities).